Prevalence and predictors of stress, anxiety, and depression among healthcare workers managing COVID-19 pandemic in Bandar Lampung - Fransisca Melyana; Teguh Pribadi; Rahma Elliya (Malahayati International Journal of Nursing and Health Science, 2021)
Background: The rapid spread of the Coronavirus 2019 and caused much mortality and also Psychological health disturbance for health workers who work on the front and direct contact with patients infected.Purpose: To know the relationship of demographic factors with the level of stress, anxiety, and symptoms of depression in health workers. Method: A quantitative study with design an analytical survey using a cross-sectional. The study took on April 2021 at Bandar Negara Husada Hospital, Lampang Province. The population was health workers with by a total sampling of 82 respondents. The instrument Depression Anxiety and Stress Scale 42 (DASS 42). Chi-square test and predictor analyzed data using binary regression test.Results: The finding of 82 respondents, with the level of anxiety, was 40.2% with the criteria of mild 3.7%, moderate 28%, and severe 11%. Stress is 25.6% with moderate criteria of 3.7% and 22% mild. Meanwhile, mild depression is 14.6%. The respondent who has a smoking history was a predictor of anxiety, while employment status was a predictor of depression.Conclusion: The prevalence of symptoms of anxiety, stress, and depression among health workers at the Bandar Negara Husada Hospital, Lampang Province during the pandemic is still relatively under control and the anticipation of their in keeps psychological healthy in the confront of a fluctuate patient with COVID-19.